Pengembangan Media Video Animasi Berbasis Kearifan Lokal pada Materi Keberagaman Makhluk Hidup di Lingkunganku Siswa Sekolah Dasar Kelas IV - Anisah Gultom; Febrianti Yuli Satriyani (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2023)
Learning Natural Sciences (IPA) on the diversity of living things in an elementary school environment is learning that can develop logical, rational, systematic and critical thinking skills through the development of the concept of the diversity of living things in the environment. Students can build meaning from the messages generated in communication on learning activities, such as oral, written, graphic. However, learning Natural Sciences (IPA) is still very difficult for elementary school students to understand, this is a concept because Natural Sciences (IPA) is still abstract. it is still difficult to understand the explanation of the material from